2023
DOI: 10.29333/pr/13168
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry teachers’ pedagogical content knowledge in teaching hybridization

Abstract: Pedagogical content knowledge, PCK, a concept in teacher education requires additional focus and attention by pre-tertiary teachers to improve teaching and learning and learners’ performance. The study adopted PCK model developed by Magnusson et al. (1999) to investigate senior high school (SHS) chemistry teachers PCK in teaching the concept of hybridization. The study adopted a qualitative approach using the case study design. Six chemistry teachers from six SHSs in the Upper West Region of Ghana were purposi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…It is also recommended to assess the students' pre-knowledge before starting the course and to diversify the didactic tools [48]. including using molecular models for a better understanding of chemical bonding, according to [37,49].…”
Section: Discussionmentioning
confidence: 99%
“…It is also recommended to assess the students' pre-knowledge before starting the course and to diversify the didactic tools [48]. including using molecular models for a better understanding of chemical bonding, according to [37,49].…”
Section: Discussionmentioning
confidence: 99%
“…According to Marifa et al (2023), the teachers' inability to exhibit higher knowledge performance in all the knowledge domains of Shulman's PCK model rendered them ineffective. Therefore, the finding of this study showed that the majority of the professionally trained chemistry teachers were more effective than the untrained chemistry teachers.…”
Section: Discussionmentioning
confidence: 99%
“…The above literature and several others have assessed science teacher trainees' PCK in Ghana with little or no available literature that sought to compare their PCK with that of untrained teachers who are equally employed by the Ghana Education Service. Marifa et al (2023) conducted a survey which assessed Chemistry teachers' pedagogical content knowledge in teaching hybridisation. The data from the survey revealed that chemistry teachers exhibited higher knowledge of instructional strategies for teaching chemistry and knowledge of the science curriculum.…”
Section: Principles and Practices Of Teachingmentioning
confidence: 99%